Review of the weaknesses in the classical model of formal organization - Bernard Sarachek, (Penerbit Universiti Kebangsaan Malaysia, 1982)
This paper discusses some of the criticisms of the classical model of formal organisations. While the model has been subjected to severe attack on its limitations, the final verdict remains favorable because the principles outlined in the model are intelectually stable.